Analyzing the postulated inhibitory effect of Manumycin A on farnesyltransferase - Hagemann, Anna; Altrogge, Philipp Klemens; Kehrenberg, Miriam Caroline Alice; Diehl, Daniel; Jung, Dominik; Weber, Lea; Bachmann, Hagen Sjard (Frontiers in Chemistry, 2022)
Manumycin A is postulated to be a specific inhibitor against the farnesyltransferase (FTase) since this effect has been shown in 1993 for yeast FTase. Since then, plenty of studies investigated Manumycin A in human cells as well as in model organisms like Caenorhabditis elegans. Some studies pointed to additional targets and pathways involved in Manumycin A effects like apoptosis. Therefore, these studies created doubt whether the main mechanism of action of Manumycin A is FTase inhibition. For some of these alternative targets half maximal inhibitory concentrations (IC50) of Manumycin A are available, but not for human and C. elegans FTase. So, we aimed to i) characterize missing C. elegans FTase kinetics, ii) elucidate the IC50 and Ki values of Manumycin A on purified human and C. elegans FTase iii) investigate Manumycin A dependent expression of FTase and apoptosis genes in C. elegans. C. elegans FTase has its temperature optimum at 40°C with KM of 1.3 µM (farnesylpyrophosphate) and 1.7 µM (protein derivate). Whilst other targets are inhibitable by Manumycin A at the nanomolar level, we found that Manumycin A inhibits cell-free FTase in micromolar concentrations (Ki human 4.15 μM; Ki C. elegans 3.16 μM). Furthermore, our gene expression results correlate with other studies indicating that thioredoxin reductase 1 is the main target of Manumycin A. According to our results, the ability of Manumycin A to inhibit the FTase at the micromolar level is rather neglectable for its cellular effects, so we postulate that the classification as a specific FTase inhibitor is no longer valid.